Impact of co-benefits on the assessment of energy related building renovation with a nearly-zero energy target - Ferreira, Marco António Pedrosa Santos (2017)
The reduction of the energy consumption and carbon emissions in the building sector is an important target for actions to mitigate the climate changes and different actions are being carried out to promote a transition to a low carbon built environment. However, present standards are mainly focused on new buildings which may result counter-productive in existing ones, due to their technical, functional and economic constraints.  One of the most common problems in the current way of assessing building renovation scenarios is that only energy savings and cost are considered, disregarding additional benefits. Many studies, based on real cases, have already highlighted the relevance of these so-called co-benefits, which can be felt at the building level (and therefore they should be considered in the definition of the renovation measures) and also at the level of society. The present investigation has been developed under the scope of IEA EBC Annex 56 project, and a method to integrate co-benefits in the evaluation of the renovation scenarios towards both the nearly-zero emissions and the nearly-zero energy objectives is proposed. It has been applied to case-studies from several European countries and based on subsequent findings recommendations for policy makers and professional owners are presented.